1986
DOI: 10.1093/nar/14.13.5513
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preincubation of HeLa cell nuclei with ATP on the degradation of mononucleosomal DNA by micrococcal nuclease

Abstract: HeLa cell nuclei with DNA labeled with [3H] thymidine have been preincubated under varying conditions and then incubated with micrococcal nuclease. Aliquots, removed at increasing times, were analyzed for mononucleosomal size DNA and for acid-soluble DNA, the ratios were plotted and a slope was determined. Preincubation with ATP and a regenerating system increased the slope 2 fold. Optimum ATP concentrations were above 0.25 mM. The ATP effect was reversed by novobiocin. No inhibition of the ATP effect was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Following electrophoresis, the gels were applied to Kodak XAR-5 film for 0.5-3 days, and the resulting autoradiographic signals were quantitated by scanning densitometry (Transidyne General). Alternatively, the regions of the gel producing major autoradiographic signals were excised, and the radioactivity was determined by a liquid scintillation spectrometer (Pentz et al, 1986).…”
mentioning
confidence: 99%
“…Following electrophoresis, the gels were applied to Kodak XAR-5 film for 0.5-3 days, and the resulting autoradiographic signals were quantitated by scanning densitometry (Transidyne General). Alternatively, the regions of the gel producing major autoradiographic signals were excised, and the radioactivity was determined by a liquid scintillation spectrometer (Pentz et al, 1986).…”
mentioning
confidence: 99%
“…It is unclear whether AMPK acts directly on the components of DNA double strand break repair pathways. However, we did observe that ATP supplementation could ameliorate the DNA repair defect caused by ATIC inhibition and there is a long history of reports that highlight the ATP dependence of repair of ultraviolet or ionizing radiation damage to DNA [3,4,6,15,24,33,35]. In addition, prior studies have shown that inhibition of AMPK activity can result in radioresistance [31,39] while AMPK activators can augment cell killing by ionizing radiation [7,26,28,36,44].…”
Section: Discussionmentioning
confidence: 88%
“…2a). This was an unexpected result, but nucleoside triphosphates have been shown to influence conformation of histones and unfolding of nucleosomes (33,34). It has been reported (14) that Tn3 transposase binds only to the Tn3 inverted repeat sequence in the presence of ATP, whereas DNA binding in the absence of ATP is both specific and nonspecific.…”
mentioning
confidence: 97%